DIGITAL TRANSFORMATION AND URBAN GOVERNANCE IN INDIA: A REVIEW OF THE SMART CITIES MISSION - Veerababu, Donthagani; Saikia, Tapan; Ganaie, Nasir Ahmad; Rath, Durga Madhab; Islam, Bodrul (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper examines the implementation of digital technologies in Srinagar under India’s Smart Cities Mission, situating the analysis within broader debates on smart urbanism. It explores how ICT-driven interventions influence governance, service delivery, and urban resilience in a conflict-affected region. The article is part and parcel of the broader debate on the subject of smart urbanism; hence, it will touch on the argument that ICT-based interventions can increase the efficiency, transparency and responsiveness of the urban governance and address the infrastructural and socio-political crises peculiar to Srinagar. This makes it an excellent example because the process of urbanising the city is not only characterised by the rage of urbanisation and lack of service, but also by a circulation of a devastated world, vulnerability to the environment and a digital divide. The research design followed in the study is a descriptive and exploratory research design, which is reliant on secondary sources; in the present case, the government reports, project reports, academic literature and existing case studies regarding the Smart City initiatives in Srinagar. It encompasses key fields of application, e.g., e-governance applications, smart traffic control, smart water and wastewater and smart metering, telemedicine, e-learning, surveillance systems and command-and-control centre. These steps are the ones to gauge their results regarding the effectiveness of management, access and actual management of the urban services. The findings of this line of discussion are as follows: digital technologies have hinted at the seemingly new improvement of areas of the city government and service delivery in question. E-governance systems have increased the level of accessibility of the citizens, mobility administration and emergency reaction systems, transparency, and smart infrastructure has increased surveillance. The second direction by which the continuity has been supported with the aid of digital devices has been in the areas of healthcare and education in times of turmoil and reduced mobility. At the same time, the paper still finds these advantages, nonetheless, to be unequal and limited by financial ability, technical capacity, a lack of coordination of institutions, regular blackouts during communications and inaccessibility to equal digital access. Having reached a conclusion, the paper has admitted that despite the bright perspectives of the technological advancements that were presented in Srinagar as part of the Smart City Mission, the inclusion and sustainable urban transformation cannot be targeted with the assistance of technology. To be effective in the war-torn and volatile environments, institutional enhancement is necessary to aid digital inclusion and resilience-based planning.